2012
DOI: 10.1155/2012/129591
|View full text |Cite
|
Sign up to set email alerts
|

Glomus intraradices Attenuates the Negative Effect of Low Pi Supply on Photosynthesis and Growth of Papaya Maradol Plants

Abstract: Low inorganic phosphorus (Pi) supply limits the photosynthetic process and hence plants growth and development. Contradictory reports exist in the literature on whether mycorrhyzal association can attenuate the negative effects of low Pi supply on photosynthesis and growth. In the present paper, the effect that low Pi supply may have on photosynthesis and growth of papaya Maradol plants was evaluated in intact plants and in those inoculated with two different strains of the arbuscular mycorrhizal fungi Glomus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Studies have shown that the application of inorganic fertilizer significantly reduced AMF α-diversity, which showed similar levels to control samples after organic fertilizer [38]. In long-term field experiments, organic and inorganic fertilizers increased and decreased the development of AMF, respectively [39].…”
Section: Effects Of Fertilizer and Arbuscular Mycorrhizal Fungi On Th...mentioning
confidence: 61%
“…Studies have shown that the application of inorganic fertilizer significantly reduced AMF α-diversity, which showed similar levels to control samples after organic fertilizer [38]. In long-term field experiments, organic and inorganic fertilizers increased and decreased the development of AMF, respectively [39].…”
Section: Effects Of Fertilizer and Arbuscular Mycorrhizal Fungi On Th...mentioning
confidence: 61%
“…For species with a short lifespan, flowering is quick and the investment in terms of energy in the reproductive organs is high (Newell & Tramer 1978). Thus, species grown in low-fertility soil, besides obtaining benefits from AMF, may also have a stimulated photosynthetic rate (Yolanda et al 2012) that allows better allocation of photoassimilates and nutrients for producing flowers (Stanley et al 1993).…”
Section: Influence Of Amf On Plants Grown In the Low-fertility Soilmentioning
confidence: 99%